Train-the-Trainer Trauma Care Program in Vietnam - Toan, Dang Quang (JMU Scholarly Commons, 2015)
By conducting a train-the-trainer trauma care program in collaboration with the Norwegian Tromsø Mine Victim Resource Centre and the Quang Tri Department of Health, Project RENEW hopes to develop the first-aid capacity of first responders in order to minimize the number of deaths and injuries caused by incidents involving landmines and unexploded ordnance.